The Effect Of Destination Images On Tourist Loyalty With Satisfaction As Mediation - Megasari Gusandra Saragih, Akhmad Taufik (International Journal of Advanced Science and Technology, 2020)
The study aims to analyze the influence of destination images on tourist loyalty with satisfaction as mediation. The sample used in this study was 150 respondents who were tourists who visited tourism in the city of Padang west Sumatra Indonesia. Purposive Sampling is used as a sampling technique. Quantitative research methods with path analysis using an analysis tool that is SEM with the help of Amos version 20.0. The results of this study indicate that the destination image influences the satisfaction and loyalty of tourists in the city of Padang west Sumatra Indonesia. Satisfaction influences tourist loyalty in Padang City. Besides, the results obtained that the tourist satisfaction variable acts as a partial mediation on the destination image variable on tourist loyalty in the city of Padang west Sumatra Indonesia .